HYGIENE PERORANGAN DAN RIWAYAT KONTAK DAN KEJADIAN KUSTA DI WILAYAH KERJA PUSKESMAS TANAH MERAH KABUPATEN BANGKALAN TAHUN 2016 - Nur Mas'Ula; Nurhaidah .; Marlik . (GEMA LINGKUNGAN KESEHATAN, 2017)
ABSTRACTLeprosy is a chronic infectious disease, caused by bacteria (Mycobacterium leprae) that attackperipheral nerves, skin and other body tissues except central nervous system. It develops as a result of closephysical contact with leprosy patients and poor condition of personal hygiene. The purpose of this study was todetermine the risk of personal hygiene and contact history with the incidence of leprosy in Tanah Merah Healthcenter in 2016.This study used case control approach. The population of this research were leprosy patients in 2015from Tanah Merah Health Center. The control population was non-leprosy patients living in Tanah Merah HealthCenter work area. Samples of this analysis were 22 cases and 22 controls and the research instruments werequestionnaires and observation sheets. Data were analyzed by calculating the Odd Ratio.The results showed that most respondents had low level of knowledge with the percentage of 56.8%,the majority of the respondents had good personal hygiene (54.5%) and the majority of the respondents hadhistory of contact with leprosy patients by 52.3%. the result of OR calculation shows that the personal hygiene(OR = 4.67) and contact history (OR = 1.73) were risk factors of leprosy incidence in Tanah Merah Health Centerin 2016.The community should maintain personal hygiene better and avoid sleeping together or close to thelepers to prevent the transmission of leprosy.Keywords : Leprosy, Personal Hygiene, History of Contact